Low-carbon optimal operation of the integrated energy system considering integrated demand response and oxygen-rich combustion capture technology - Ji, Xiu; Li, Meng; Li, Meiyue; Han, Huanhuan (Frontiers in Energy Research, 2024)
In view of the current operating constraints and environmental pollution problems of traditional units, oxygen-rich combustion capture technology is introduced to transform gasfired units, demand response technology is used on the load side, the energy conversion equipment such as power-to-gas equipment is combined to form an integrated energy system, and then a low-carbon optimization approach of the integrated energy system is proposed in this article. Firstly, the system architecture is constructed, and a model with oxygen-rich combustion unit and integrate demand response is established. Secondly, a power-to-gas equipment model considering the reaction waste heat utilization and oxygen recovery is established. Finally, a stepped carbon trading mechanism is introduced to establish a lowcarbon economic scheduling model for the integrated energy system with the goal of minimizing the operating cost of the integrated energy system. The simulation results show that the total cost and carbon emissions of the integrated energy system are reduced by 6.44% and 44.24% respectively under this model. At the same time, the operation adjustment capability and the oxygen production efficiency of the internal units of the system are improved.